Measuring the pore structure of cement asphalt mortar by nuclear magnetic resonance. (15th April 2017) - Wang, Yong; Yuan, Qiang; Deng, Dehua; Ye, Tao; Fang, Lei
Highlights: Pore structure of CA mortar was characterized by nuclear magnetic resonance (NMR). Surface relaxivity of CA mortar was calibrated by mercury intrusion porosity (MIP) test under the pressure of 0–0.4 MPa. Pore size distribution of CA mortars presented three peaks. Abstract: Cement asphalt (CA) mortar, a porous and organic-inorganic composite, has been widely used in high-speed rail. Since the high content of asphalt and its low strength, mercury intrusion porosity (MIP) may not be applicable to measure the complete pore structure of cement asphalt (CA) mortar. In this paper, nuclear magnetic resonance (NMR) relaxometry method was used to measure the pore structure of CA mortar with various water-to-cement (W/C) ratio and asphalt to cement (A/C) ratio. The porosity obtained by MIP under the pressure of 0–0.4 MPa was used to infer the surface relaxivity which is a key parameter for the calculation of pore size in NMR relaxometry method. Results showed that a value of 40 μm/s can be adopted as the surface relaxivity of CA mortar. Pore size distribution of CA mortars presented three peaks. The peaks did not shift with w/c ratios, but got higher with the increase in W/C ratios. Low A/C ratio leads to coarser pore structure of CA mortar.